Pengaruh Konflik Kerja dan Beban Kerja Terhadap Kinerja Karyawan Melalui Self-Efficacy Sebagai Variabel Intervening Divisi Personalia PT Kerta Rajasa Raya Sidoarjo - Galih Laksana Ardi; Tan Evan Tandiyono (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to prove and analyze the influence of work conflict and workload on employee performance through self-efficacy as an intervening variable in the personnel division of PT Kerata Rajasa Raya in Sidoarjo. This research is a type of causal explanatory research which aims to prove and analyze the causal relationship between two or more variables.The respondents in this study were 63 personnel employees, who were selected through Accidental Sampling from a population of 63 people, Data was collected through a questionnaire and then the data was sent to SmartPLS 4. It can be concluded that this research has five hypotheses and four variables, of which there are two variables that do not significantly influence employee performance and self-efficacy. However, there is one variable that has a significant effect on employee performance, namely self-efficacy on employee performance